1999
DOI: 10.1177/002215549904701005
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Organic Anion Transporting Polypeptide 2 (Oatp2) in Capillary Endothelium and Choroid Plexus Epithelium of Rat Brain

Abstract: In this study we investigated the distribution of a recently cloned polyspecific organic anion transporting polypeptide (Oatp2) in rat brain by nonradioactive in situ hybridization histochemistry and immunofluorescence microscopy. The results demonstrate that Oatp2 is expressed in brain capillary and in plexus epithelial cells. At the blood-brain barrier (BBB), Oatp2 expression could be co-localized with the endothelial marker vWF (von Willebrand factor) but not with the astrocyte marker GFAP (glial fibrillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
200
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(217 citation statements)
references
References 28 publications
9
200
0
Order By: Relevance
“…4, the immunoreactivity was detected in restricted brain regions. In addition, a previous immunohistochemical study showed that anti-oatp2 antibody gave intense immunoreactivity on endothelial cells of cerebral capillaries, whereas this antibody exhibited only a weak band of oatp2 in a similar amount (30 lg) of rat brain membrane fraction by western blotting (Gao et al 1999). mRNA expression of oatp2 in mouse brain is greater than that of oatp3 (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…4, the immunoreactivity was detected in restricted brain regions. In addition, a previous immunohistochemical study showed that anti-oatp2 antibody gave intense immunoreactivity on endothelial cells of cerebral capillaries, whereas this antibody exhibited only a weak band of oatp2 in a similar amount (30 lg) of rat brain membrane fraction by western blotting (Gao et al 1999). mRNA expression of oatp2 in mouse brain is greater than that of oatp3 (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…3) suggested mouse oatp3 to be localized at the brush-border membrane of choroid plexus. Furthermore, rat oatp2 is localized at the basolateral membrane of choroid plexus epithelial cells (Gao et al 1999), and mouse oatp2 was also detected in choroid plexus (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most CAPs are cationic by virtue of the presence of lysine, arginine and/or histidine and usually composed of 12-50 amino acids. The bactericidal effect of many CAPs is thought to be due to the action on the cytoplasmic membrane of the susceptible bacteria, possibly through the formation of pores or destabilization of the membrane bilayer structure leading to lysis of the cell [4,5]. Some CAPs such as buforin 11 [6], indolicidin [7], apidaecin [8], PR 39 [9], PR 26 [10], bactenecin [11] and lactoferricin B [12,13] have been reported to have intracellular targets.…”
Section: Introductionmentioning
confidence: 99%
“…Oatp1 is expressed, in addition to the sinusoidal membrane of hepatocytes [9], in the apical membrane of the proximal tubule [10] and in the apical membrane of the choroid plexus [11]. Oatp2 protein was detected in rat liver hepatocytes, endothelial cells of the blood\brain barrier [12][13][14] and the choroid plexus [12]. On the basis of Northern-blot analysis, Oatp3 is expressed in the kidney, liver and the retina [4].…”
Section: Introductionmentioning
confidence: 99%